ChemInform Abstract: Two New Retigerane‐Type Sesterterpenoids from the Lichen Leprocaulon microscopicum. Issue 28 (June 2016) - Millot, Marion; Martin‐de‐Lassalle, Marie; Chollet‐Krugler, Marylene; Champavier, Yves; Mambu, Lengo; Chulia, Jose‐Albert; Lacaille‐Dubois, Marie‐Aleth
Abstract: Two new compounds (I) and (II) are isolated, possessing a rare pentacyclic carbon skeleton typical for lichen metabolism, and quite unusual in the vegetal kingdom.